2022
DOI: 10.1126/sciadv.abn6064
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic particle dam for direct visualization of SARS-CoV-2 antibody levels in COVID-19 vaccinees

Abstract: Various COVID-19 vaccines are currently deployed, but their immunization varies and decays with time. Antibody level is a potent correlate to immune protection, but its quantitation relies on intensive laboratory techniques. Here, we report a decentralized, instrument-free microfluidic device that directly visualizes SARS-CoV-2 antibody levels. Magnetic microparticles (MMPs) and polystyrene microparticles (PMPs) can bind to SARS-CoV-2 antibodies simultaneously. In a microfluidic chip, this binding reduces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…A recent study that assessed antibody titers in COVID-19 patients showed that the spike RBD-specific IgG was ∼11.4 μg/mL in most patients even after 41 days of infection . In addition, a study of 91 healthy but vaccinated people without a history SARS-CoV-2 infection showed that mRNA-vaccinated persons have 1.1 μg/mL as the mean range of anti-SARS-CoV-2 spike RBD IgG . This indicates our sensor is sufficiently sensitive (LOD: 0.42 ng/mL) to quantify anti-SARS-CoV-2 spike RBD IgG antibodies in both COVID-19 patients and vaccinated healthy individuals.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…A recent study that assessed antibody titers in COVID-19 patients showed that the spike RBD-specific IgG was ∼11.4 μg/mL in most patients even after 41 days of infection . In addition, a study of 91 healthy but vaccinated people without a history SARS-CoV-2 infection showed that mRNA-vaccinated persons have 1.1 μg/mL as the mean range of anti-SARS-CoV-2 spike RBD IgG . This indicates our sensor is sufficiently sensitive (LOD: 0.42 ng/mL) to quantify anti-SARS-CoV-2 spike RBD IgG antibodies in both COVID-19 patients and vaccinated healthy individuals.…”
Section: Resultsmentioning
confidence: 64%
“…This dilution is advantageous because it minimizes matrix effects and is usually done in immunoassays to decrease background noise. Our method provided a better LOD than a similar fluorescence-based antibody detection method (50 ng/mL) 16 and a microfluidic device-based method (13.3 ng/mL), 29 and a comparable LOD (0.3 ng/mL) to an enzyme immunoassay for quantification of anti-SARS-CoV-2 IgG. 30 There are also methods that have been reported with lower LODs than this method, such as 0.24 pg/mL using a Simoa HD-X Analyzer for SARS-CoV-2 antibody detection.…”
Section: Methodsmentioning
confidence: 83%
“…We summarized the comparative evaluation of our platform with the previously reported systems in Table S4 . Compared with the previous results, our system shows similar LOD value with easy colorimetric analysis by naked eye, cost-effective automatic operation, versatile nucleocapsid-specific monoclonal antibodies capable of distinguishing four kinds of SARS-CoV-2 variants [26] , [27] , [28] , [29] .…”
Section: Resultsmentioning
confidence: 65%
“…The antigen-antibody binding was carried out within a test tube, enabling an immediate and synchronal contact of antigen- and antibody-conjugated beads and achieving a low detection limit of less than 100 copies mL −1 within 30 s. The detection signal was then obtained by the naked-eye reading of the red color intensity, which was potentially affected by subjective interpretation. Subsequently, to fulfill quantitative measurement while maintaining a simple and user-friendly interface, Wu et al demonstrated a novel microfluidic chip with a particle dam for quantitative visualization of SARS-CoV-2 antibody levels from the accumulation length of the microparticles functionalized with antibodies [ 16 ]. However, despite promising progress, most of these POC platforms enable naked-eye qualitative detection or additional instrument-assisted quantitative detection.…”
Section: Introductionmentioning
confidence: 99%